Truly understood - Peacocke, Christopher (Oxford : Oxford University Press, 2008)
What is it to be able to think about the material world, about oneself, and about other people? Christopher Peacocke argues that our concepts are to be explained in terms of the conditions in which they refer to aspects of the world. Reference and truth are fundamental in understanding.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Comprehension (Theory of knowledge); Truth; Reference (Philosophy)